Foreign Bias in the Global Portfolio Investment of Selected OIC Countries - Md Elias, Nura Lina (Information Management and Business Review, 2023)
Home bias reflects the propensity of investors to invest substantially in the domestic market. When investing abroad investors exhibit foreign bias, a tendency to overweight certain foreign markets based on their preferences. A thorough review of the literature reveals that foreign bias has not been thoroughly investigated in emerging countries, especially in the context of OIC countries. The purpose of this research is to examine the determinants of foreign bias in the global portfolio investment of selected OIC countries. An unbalanced bilateral panel data of 12 OIC countries’ outward equity investment in 74 host countries from the year 2001 to 2016 is analyzed. Cross-sectional analysis shows that OIC countries exhibit higher foreign bias towards their OIC counterparts especially in the MENA region. The results suggest, OIC countries not only exhibit foreign bias but also demonstrate regional bias. System Generalized Method of Moments (GMM) empirically shows that foreign bias is possibly explained by factors related to financial market openness, familiarity, information asymmetry, and global financial crisis. This study has a significant implication for the investors, fund managers and the regulators of the OIC countries. Investors and fund managers in OIC countries should be aware of the existence of foreign bias in their global portfolio investment that may potentially reduce the benefits of optimal diversification. It is a call for policymakers in the OIC countries to convince their local investors that international portfolio diversification offers risk sharing and eventually increases investment return.